Managing change : enquiry and action - Beech, Nic (Cambridge : Cambridge University Press, 2017)
Managing Change: Enquiry and Action, Australasian edition offers a fresh perspective of change theory with contemporary examples providing students with the tools they need to navigate the complexities of change within organisations. The book features notions of innovation, disruption and agile learning that are necessary in an intensified business world. Using an enquiry-action framework, the text is separated into three parts: diagnosing, explaining and enacting to combine theory with the practical tools needed to understand and manage change. Cases reinforce student understanding and focus on actions and outcomes while a selection of fifteen extended cases bring different concepts together. Written by leading professionals, Managing Change: Enquiry and Action, Australasian Edition is an essential resource for students looking to develop a strong skills base that can be employed in practice.
Part A: Foundations. 1. Practising change management -- 2. Change approach: concepts and framework -- 3. Innovation -- Part B: Diagnosing. 4. Understanding the change context: internal and external factors -- 5. Clarity and ambiguity -- 6. Engagement and vitality -- 7. Stakeholder positioning and dynamics -- 8. Culture, habits and unlearning -- Part C: Enacting Change. 9. Choosing/adopting an approach to change -- 10. Changing structure -- 11. Identity and change -- 12. Choosing customers and competitors -- 13. Changing processes -- 14. Aligning people and activities -- 15. Learning and developing -- 16. Conversations and stories -- Part D: Explaining. 17. Developing and interpreting evidence -- 18. The enquiry-action framework in practice -- Part E: Extended Cases.
Title from publisher's bibliographic system (viewed on 19 Sep 2018).
Keywords: elektronické knihy; electronic books; Organizational change; Organizational change -- Management